ZONATION OF PRIME AGRICULTURE COMODITIES IN MAYBRAT REGENCY-WEST PAPUA - Sagrim, Meky (Jurnal Pertanian, 2020)
Developing agricultural sector needs integrated plans based on quality land resources and environment, human resources, and marketable oriented for farmers prestige and nation welfare. A field research using observatory and interview (semi-structured) methods done. In one hand, focus group discussion and/or rapid rural appraisal employed in targeted villages where respondents met. The finding of this research was that there were six agricultural developing zones, i.e. Agrosilvopastoral, Agroecotourism, Non-farming industry, Midle and small Entrepreneur zone, Ecotourism, and food store. Deciding agricultural commodity for crops, horticultural, fisheries, livestock and forestry were determined based on landuse suitability of in-citu areas. Creating food store has been done in order to promote Maybrat regency as food stability and food independence, which is in line with national program of food national resistant. Keywords: Zones, Agrosilvopastoral, Agroecotouris, Non-Farm, Ecotourism, Food store, Maybrat